Establishment Of A Hypertension Care Family Groups In Hamlet 7, Bendogerit Sub-District, Blitar City - Mujito, Mujito; Sepdianto, Tri Cahyo; Martiningsih, Wiwin (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
Hypertension is known as the silent killer which is a risk factor for early death. Hypertension can lead to heart failure and cerebrovascular disorders. This is because the symptoms often go unnoticed. The purpose of the community partnership program for hypertension care family groups was to increase family awareness, increase cadre capacity, and establishment of hypertension care family groups. The method used the empowerment of family potential as an intervention strategy for health promotion in the prevention and controlling of hypertension to obtain the results, namely: (1) Health education to families at risk of hypertension from the results of observations obtained that the attendance rate of participants was 100%, and the involvement of participants was 60%. (2) Cadre training using the lecture question and answer method and demonstration of the post-test, there was an increase in knowledge that enough category was only 10%, the good category increased to 80% and the very good category increased to 10% and there was an increase in skill ability, namely 80% were able to take measurements of blood pressure, 50% were able to calculate BMI, 50% were able to measure cholesterol, blood sugar, uric acid, and 100% were able to record KMS FR-PTM. (3) Hypertension care family groups were established in hamlet 7, Bendogerit sub-district. The establishment of the hypertension care family groups used a development approach of Active Alert village, namely from, by, and for the community. Hypertension risk families are expected to participate more actively in getting services for detecting hypertension risk factor